Study on heat transfer behavior and thermal breakage characteristic of the charge in ball mills - Tongqing Li; Zixin Yin; Guiyi Wu (Advances in Mechanical Engineering, 2021)
Ball mill is the widely used comminution device for the size reduction of iron ore particles, yet the underlying mechanisms of heat transfer and thermal breakage inside the mills heretofore are not deeply understood. Therefore, the Discrete element method was carried out to study the effect of operating parameters on charge temperature, and the batch grinding experiments of iron ores were conducted to verify the heating temperatures using a laboratory ball mill. Results show that increasing mill speed will result in the charge temperature increasing initially and then decreasing. The temperature fields of the charge and load behavior remain approximately the same for the different ball filling. The main findings of this study are that the heating temperature can contribute to enhancing the breakage behavior of iron ore particles, and correspondingly the optimal feed sizes for different heating temperatures are determined to be 2.48 mm, 2.63 mm, 2.78 mm, and 3.59 mm, respectively.